UJI ADAPTASI LIMA VARIETAS UNGGUL CABAI MERAH KERITING DI LAHAN KERING DENGAN TEKNOLOGI PROLIGA - Anggun Yossika Naibaho; Maria Heviyanti; Murdhiani Murdhiani; Rina Manarany (University of Prof. Dr. Hazairin, SH, 2021)
This study aims to determine the growth and yield of five varieties of curly red chilies through proliga technology on dry land. held at the Experimental Garden of the Faculty of Agriculture, Samudra University, Langsa City, Aceh province which took place from July to November 2020. Using a non-factorial randomized block design (RAK) using curly red chili seeds, superior varieties of F1 hybrids with five varieties, namely Lado F1, PM 999 F1, Taro F1, Kastilo F1, and Lentur F1. The parameters observed in this study included: plant height, number of branches, flowering age, harvest age, fruit weight per sample, and fruit weight per plot. The results showed that the growth and production of five superior varieties of curly red chili on dry land with proliga technology had no significant effect on plant height at 2 WAP and 4 WAP, the number of branches at 5 WAP, flowering age (HST) fruit weight per sample, and fruit weight per plot. Meanwhile, the number of branches, age 7 WAP and harvesting age (HST) had a significant effect. The best growth and production of the five superior varieties of curly red chili on dry land with proliga technology is V1 (Lado F1) with the highest yield potential, namely 6.64 tonnes/ha.